2018
DOI: 10.1016/j.celrep.2018.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mitochondrial Dysfunction Activates the Integrated Stress Response to Induce Fibroblast Growth Factor 21

Abstract: SummaryStress adaptation is essential for neuronal health. While the fundamental role of mitochondria in neuronal development has been demonstrated, it is still not clear how adult neurons respond to alterations in mitochondrial function and how neurons sense, signal, and respond to dysfunction of mitochondria and their interacting organelles. Here, we show that neuron-specific, inducible in vivo ablation of the mitochondrial fission protein Drp1 causes ER stress, resulting in activation of the integrated stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 53 publications
(85 reference statements)
2
70
0
Order By: Relevance
“…The presence of fibroblast growth factor 21 (FGF21) within the biomarker profile of PD is especially noticeable. Indeed, FGF21 has recently been related to dysfunctional MQC in neurons and has shown to be induced in brains of murine models of tauopathy and prion disease [155]. Thus, it is proposed that FGF21 may function as a "mitokine" and serve as a biomarker of mitochondrial dysfunction in the brain [155].…”
Section: Circulating Mitochondrial-derived Vesicles Systemic Inflammmentioning
confidence: 99%
“…The presence of fibroblast growth factor 21 (FGF21) within the biomarker profile of PD is especially noticeable. Indeed, FGF21 has recently been related to dysfunctional MQC in neurons and has shown to be induced in brains of murine models of tauopathy and prion disease [155]. Thus, it is proposed that FGF21 may function as a "mitokine" and serve as a biomarker of mitochondrial dysfunction in the brain [155].…”
Section: Circulating Mitochondrial-derived Vesicles Systemic Inflammmentioning
confidence: 99%
“…Recent data indicate that to fully comprehend the phenotypic manifestations of mitochondrial diseases, it is crucial to take into account metabolic stress responses of the affected cells (Khan et al, 2017;Nikkanen et al, 2016;Restelli et al, 2018;Suomalainen & Battersby, 2018). A common feature observed in mouse models of mitochondrial diseases characterized by defects in mtDNA gene expression is the upregulation of the mitochondrial folate cycle and the serine biosynthesis pathway (Kuhl et al, 2017;Nikkanen et al, 2016).…”
Section: Deficiency Of the M-aaa Protease In Astrocytes Induces Infmentioning
confidence: 99%
“…FGF21, which has been recognized as a prime lipid catabolic factor, plays an important role in regulating energy balance [20]. In recent years, it has been found that FGF21 could be an early biomarker for dysregulated mitochondrial dynamics and endoplasmic reticulum (ER) stress conditions and that it induces glial cells to promote remyelination in response to CNS disorders [40,41].…”
Section: Discussionmentioning
confidence: 99%